1991
DOI: 10.1042/bj2750335
|View full text |Cite
|
Sign up to set email alerts
|

The reactivities and ionization properties of the active-site dithiol groups of mammalian protein disulphide-isomerase

Abstract: 1. The number of reactive thiol groups in mammalian liver protein disulphide-isomerase (PDI) in various conditions was investigated by alkylation with iodo[14C]acetate. 2. Both the native enzyme, as isolated, and the urea-denatured enzyme contained negligible reactive thiol groups; the enzyme reduced with dithiothreitol contained two groups reactive towards iodoacetic acid at pH 7.5, and up to five reactive groups were detectable in the reduced denatured enzyme. 3. Modification of the two reactive groups in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 33 publications
1
62
1
Order By: Relevance
“…The two thioredoxin-like (CGHC) sequences of PDI have been characterized as the active sites for its isomerase activity [28]. In vitro experiments have shown that PDI can accelerate oxidation and can unscramble inappropriate disulfide bonds [27].…”
Section: Protein Disulfide Isomerasesmentioning
confidence: 99%
“…The two thioredoxin-like (CGHC) sequences of PDI have been characterized as the active sites for its isomerase activity [28]. In vitro experiments have shown that PDI can accelerate oxidation and can unscramble inappropriate disulfide bonds [27].…”
Section: Protein Disulfide Isomerasesmentioning
confidence: 99%
“…The two thioredoxin-like -CGHC-sequences and the peptide segment 451^476 in the C-terminal region of PDI have been characterized to be the active sites for its isomerase activity [15] and the peptide binding site [16] respectively. PDI alkylated at the active site thiols shows little isomerase activity but retains nearly full ability for increasing reactivation and decreasing aggregation during refolding of denatured GAPDH as that of native PDI [17], suggesting that the chaperone activity of PDI is independent of its -CGHC-active sites.…”
Section: Chaperone Activity Of Protein Disul¢de Isomerasementioning
confidence: 99%
“…In addition, PDI suppresses aggregation of rhodanese during thermal denaturation. The above properties are entirely consistent with the de¢nition by Ellis of chaperones [1] and fully meet the four criteria proposed by Jakob and Buchner [14] for characterization of a protein as a molecular chaperone.The two thioredoxin-like -CGHC-sequences and the peptide segment 451^476 in the C-terminal region of PDI have been characterized to be the active sites for its isomerase activity [15] and the peptide binding site [16] respectively. PDI alkylated at the active site thiols shows little isomerase activity but retains nearly full ability for increasing reactivation and decreasing aggregation during refolding of denatured GAPDH as that of native PDI [17], suggesting that the chaperone activity of PDI is independent of its -CGHC-active sites.…”
mentioning
confidence: 99%
“…The pK a value of the aromatic thiols were expected to be similar to that of PDI. 135 As most protein folding assays are performed in aqueous media close to neutral pH, the aromatic thiols selected were expected to be soluble at pH 7 in both the thiol and disulfide form.…”
Section: Synthesis Of Aromatic Monothiols (1-4) and Their Correspondimentioning
confidence: 99%